Understanding Parental Involvement as a Correlate of Students’ Academic Achievement: A Case Study in a National High School - Charleen Vie Taganas; Karen Luz Yap; Leomarich F Casinillo (Indonesian Journal of Educational Research and Review, 2026)
Limited parental involvement in academic activities may affect students’ motivation, learning responsibility, and academic achievement. This study aimed to examine parental involvement as a correlate of Senior High School students’ academic achievement at Trinidad Mapa-Gupana National High School, Tubajon, Dinagat Islands, Philippines. A descriptive-correlational research design was employed involving 147 respondents consisting of students, parents, and Senior High School teachers across three academic years. Data were collected using researcher-developed questionnaires and teacher open-ended questions, then analyzed using frequency, percentage, weighted mean, Chi-square, Pearson correlation, Spearman’s rho, and Cramér’s V. The findings showed that parents demonstrated high involvement in homework supervision and school activities but low involvement in communicating expectations and setting academic goals. Parental educational attainment was significantly associated with homework supervision, while marital status was significantly related to expectation communication and participation in school activities. Participation in school activities showed a significant negative relationship with students’ average grades. The study implies that schools should strengthen structured parent–teacher collaboration, academic goal setting, and accessible monitoring systems to support students’ academic progress.